Design of motor-driven precision seed-metering device with improved fuzzy PID controller for small peanut planters - Yu, Yan; Hu, Yanrui; Shang, Shuqi; Diao, Linsong; Ge, Ruchao; Zhang, Xing (International Journal of Agricultural and Biological Engineering, 2023)
Traditional passive ground wheel drive of peanut planters has displayed poor high-speed seeding performance and the slippage caused in case of sticky and wet soil. Given this, an integrated electric-driven precision seed metering device and controller were designed, which features the application of improved fuzzy PID algorithm. Based on a small peanut planter with one ridge width and duplicate rows, the servo motor drive is used to replace the traditional passive ground wheel. In addition, the satellite speed measurement is employed to complete the electric driving and controlling modification of the seed meter and precise seeding control. A working process mathematical model for the peanut metering device was established to conduct motor speed and field tests which aim at comparing performances between the conventional and the improved fuzzy PID controls. The motor speed trial shows that the average error of the actual speed of the improved fuzzy PID motor was ±1 rad/min, and the coefficient of variation was less than 1%. Against the conventional one, it can better suppress overshoot and improve the response speed. The stable output speed can still be obtained even in case of step changes. Field tests show that when working at medium and low speeds, the qualified rate of plant spacing was greater than 98%, and the rate of missed sowing is <2%; while working at high speed, the qualified rate was greater than 94%, and the rate of missed sowing was less than 4%. The average plant spacing qualification rate of the seed device increased by 6.72%; compared with other electric-driven peanut seed meters, the plant spacing qualification rate increased by 4% during high-speed sowing. In summary, this study has provided an effective technical reference for high-speed precision planting of peanuts. Keywords: peanut planter, precision seeding, control system, improved fuzzy PID DOI: 10.25165/j.ijabe.20231601.7859 Citation: Yu Y, Hu Y R, Shang S Q, Diao L S, Ge R C, Zhang X. Design of motor-driven precision seed-metering device with improved fuzzy PID controller for small peanut planters. Int J Agric & Biol Eng, 2023; 16(1): 136–144.